Cardiovascular disease awareness among Indonesian young adults: A cross-sectional study - Septa Meriana Lumbantoruan; Deby Kristiani Uligraff (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Cardiovascular diseases (CVDs) are becoming more prevalent worldwide each year, contributing to the leading cause of mortality in both men and women. Awareness of CVD is low, particularly in developing countries. Objectives: This study aimed to identify key variables that determine CVD awareness among young adults. Methods: This study used a cross-sectional, descriptive correlational design and was conducted in accordance with STROBE guidelines. Data were collected across Indonesia via social media from late November 2022 to February 2023. CVD awareness was assessed using the Attitude-Belief-About-Cardiovascular-Disease (ABCD) Risk Questionnaire. Data were analyzed using univariate, bivariate (Fisher’s, Wilcoxon, Spearman, and Kruskal-Wallis), and regression (ordinary least squares and robust) analyses. Results: 270 respondents participated in this study, with average age of 26.88 (SD = 5.55). The mean CVD awareness score was 55.27 (SD = 5.85). Gender, educational background, and body mass index (BMI) all played a role in CVD awareness. Female sex was associated with lower awareness (OLS: B = -1.99, p < 0.001; robust: B = -1.62, p < 0.01), while university attendance was associated with higher awareness (robust: B = 1.64, p = 0.03). Higher BMI was the strongest and most consistent predictor of CVD awareness across models (OLS: B = 0.19, p < 0.001; robust: B = 0.18, p < 0.001). Conclusion: Young adults (aged ≥ 18-39) in Indonesia demonstrated adequate knowledge of CVD risk factors; however, females, those with lower educational attainment, and individuals with normal weight showed lower levels of CVD awareness. Targeted health education and CVD screening programs are needed for these groups. Nurses play a pivotal role in bridging these awareness gaps by implementing tailored health education initiatives and proactive, community-based screening programs that specifically address the needs of these high-risk subgroups to promote early detection and long-term cardiovascular health.